SECONDARY PREVENTION TERHADAP MOTIVASI KLIEN HIPERTENSI DALAM PENGONTROLAN TEKANAN DARAH - yenni, yenni; Reni, Reni (REAL in Nursing Journal, 2018)
The aims of this study to determine the effect of secondary prevention on the motivation of hypertension clients in controlling blood pressure. Conducted from February to March 2018 in the Neurology Room and Internation of RSUD Prof. Dr. MA. Hanafiah Batusangkar BC Tanah. This type of research was an experiment with a Quasi Experiment Design Nonequivalent Control Group design. The study population was moderate hypertension patients aged 18-59 years, taken by purposive sampling as many as 10 intervention groups and 10 control groups. Bivariate analysis using the Mann-Whitney test. Statistical tests show there is a secondary prevention effect on the motivation of hypertensive clients in controlling blood pressure. p value = 0.012 (p value <0.05). The average value of the motivation of the intervention group was 69.0, SD 8.313,  Mean Rank 13.8 and the control group 58.70, SD 3.683,  Mean Rank 7.20. It can be concluded that there is an effect of the secondary prevention implementation on the motivation of hypertensive clients in controlling blood pressure. It is expected that nurses in hospitals and health centers to be able to use secondary prevention as one strategy in increasing the motivation of clients to control blood pressure.Keywords: motivation, secondary prevention, blood pressure